“Homeland is a Matter of Accent”, a Reading of The Voice Over Present in Two Chronicles by José Ignacio Cabrujas - Ardila Cabrera, Vanessa (2023)
José Ignacio Cabrujas (1937-1995) is a fundamental reference in the Venezuelan cultural contex of the 20th century. The constant theme in all his productions is Venezuela, especially in the chronicle, where he openly questions the political, economic, social and cultural conformation of a country marked by contradictory historical facts. For this reason, a reading of the voice over present in two of his chronicles allows an approach to the author's language in order to show how, through the use of colloquial and everyday expressions, Cabrujas portrays the reality of a country from its speech act. The voice over in both chronicles are analyzed according to the theoretical postulates Mario García-Page (2008). With this analysis we outline an approach to Cabrujas ideological-semantic configuration, which seems to be already present in the affirmation of his character Purificación in Acto cultural (1976): “Homeland is a matter of accent”.